Evaluating the benefits and impact of large-scale maize production initiatives in the Amatole District Municipality, Eastern Cape - Mfule, Zintle (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.